Universalism and racism in Kant’s critical philosophy - Andree Hahmann (Rivista di Estetica)
This paper discusses the presence of potentially racist statements in Kant’s philosophical work and the complexity of interpreting their implications for his philosophical system. The goal is to correct a common misunderstanding about the apparent conflict between Kant’s moral universalism and these seemingly racist statements. In addition, the problems arising from Kant’s universalist framework that can lead to pejorative judgments about non-white or non-European cultures are illuminated. In conclusion, it is emphasized that there is an urgent need to examine whether these judgments qualify as a form of racism and how they relate to Kant’s critical systematics.